Transvestism in a person with learning disabilities presenting with behavioural problems. - Thomas PR; Dealwis K (Journal of Intellectual Disability Research, 1995)
A case of transvestism is reported in a 47-year-old man with learning disabilities. He had developed encephalitis in childhood, which had resulted in moderate learning disabilities and epilepsy, and had been living in institutions from the age of six. He did not have any chance to express his sexual desire and this frustration manifested as aggressive behaviour. Recently, he moved to a community home and his deviant sexual behaviour became apparent. Management of his problems involves organizing a behavioural programme linking his cross dressing with aggressive behaviour.